Assessing the Decision to Invest Mosque Funds in Bank: A Case Study of Mosque Financial Practices in Takalar Regency - Nurlinda Agustin; Agusdiwana Suarni; Muhammad Khaedar Sahib (IECON: International Economics and Business Conference, 2024)
This study explores the factors influencing mosque management decisions regarding the placement of funds, considering options such as Islamic banks, conventional banks, or storage at the board's residence. The research emphasizes compliance with sharia principles and management efficiency as key decision-making criteria. A qualitative approach is employed using a case study methodology. Data collection techniques include in-depth interviews, direct observation, and analysis of mosque financial documents, with thematic analysis applied to interpret the findings. The results reveal that 50% of mosque funds are stored in the board's house, 35% in Islamic banks, and 15% in conventional banks. These findings highlight the significant reliance on informal storage methods, reflecting challenges such as limited access to financial institutions or concerns over administrative complexity. The study contributes to the development of more professional and transparent mosque financial management practices, which are crucial for enhancing public trust. Additionally, it offers a fresh perspective on mosque financial practices by focusing on fund placement in banking institutions, particularly within the Takalar region. The research addresses existing gaps in the study of mosque financial management and underscores the importance of aligning fund management with sharia principles while improving operational efficiency. Future studies could explore the impact of financial literacy among mosque boards and the role of regulatory frameworks in shaping fund placement decisions.